Telecommunication Reform in Ghana - Haggarty, Luke; Shirley, Mary M.; Wallsten, Scott (World Bank, Washington, DC, 2014)
In 1996 Ghana privatized its incumbent telecommunications firm by selling 30 percent of Ghana Telecom to Telekom Malaysia, licensing a second network operator, and allowing multiple mobile firms to enter the market. The reforms yielded mixed results. Landline telephone penetration increased dramatically while the number of mobile subscribers surpassed even this higher level of fixed line subscribers. On the other hand, the network did not reach the levels the government hoped, the second network operator never really got off the ground, and the regulator remained weak and relatively ineffective. The sustainability of competition is unclear. The government ended Telekom Malaysia's management of Ghana Telecom and has invited Norway's Telenor as a strategic partner. What this means in practice remains unclear, and the process for selecting Telenor lacked any transparency. Meanwhile, some of the mobile firms are in precarious financial positions. Competition is still relatively strong, but its sustainability will depend on the government's future commitment to ensuring it.